Textural and oceanographic aspects of the sandy beaches of South coast of Santa Catarina, Brazil - HORN FILHO, NORBERTO OLMIRO; SCHMIDT, ANDREOARA DESCHAMPS; Estevam, Cristian Nunes; Oliveira, Ulisses Rocha de; Diebe, Vinícius Fleming Corradini (Quaternary and Environmental Geosciences, 2020)
This study aims to describe the textural and oceanographic aspects of the foreshore zone of the beaches located between the municipalities of Passo de Torres and Balneário Rincão, at South coast of Santa Catarina. Oceanographic and textural parameters were collected at 41 sites, arranged on 22 beaches that extend out on 77,4 km of coastline. The field work was conducted in December 2007. The Sysgran software analyzed the textural data, revealing high homogeneity of grain size, predominance of fine sand, with quartzose sediments, reddish brown color (2.5YR5/3) in 66% of the samples and brown color (10YR5/3) in 34% of the samples, besides reducing amount of organic matter and biodetritic carbonate. In general, the sediments are well sorted, mesokurtic and with skewness approximately symmetrical. Regarding the source area, it should be noted that the coastal plain of the South coast of Santa Catarina comprises a wide barrier-lagoon depositional system of Holocene age, in which the sediments in general show high maturity. Regarding the coastal oceanographic aspects, the rectilinear shape of the coastline, as well as the predominant dissipative morphodynamic stage and a system of well-developed coastal dunes in most of the sites examined, corroborate with the textural and compositional homogeneity resulting from the frequency and intensity of the marine dynamic agents, winds and supply of lithoclastic sediments.